2002
DOI: 10.1182/blood.v99.2.672
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor inhibits the mitochondria-dependent activation of caspase-3 in neutrophils

Abstract: The exact mechanism of apoptosis in neutrophils (PMNs) and the explanation for the antiapoptotic effect of granulocyte colony-stimulating factor (G-CSF) in PMNs are unclear. Using specific fluorescent mitochondrial staining, immunofluorescent confocal microscopy, Western blotting, and flow cytometry, this study found that PMNs possess an unexpectedly large number of mitochondria, which are involved in apoptosis. Spontaneous PMN apoptosis was associated with translocation of the Bcl-2-like protein Bax to the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
188
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(209 citation statements)
references
References 52 publications
19
188
0
1
Order By: Relevance
“…3,5,6 However, in neutrophils, these organelles hardly play a role in energy metabolism as they do in other cells. This conclusion was derived from the experiment shown in Figure 1, where ATP concentrations in neutrophils were measured under various conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,5,6 However, in neutrophils, these organelles hardly play a role in energy metabolism as they do in other cells. This conclusion was derived from the experiment shown in Figure 1, where ATP concentrations in neutrophils were measured under various conditions.…”
Section: Resultsmentioning
confidence: 99%
“…from four independent experiments During the neutrophilic lineage maturation, HL-60 cells gain tubular mitochondria and lose cytochrome c expression Despite a limited role of neutrophil mitochondria in cellular metabolism, our recent studies have suggested that these organelles might be involved in neutrophil cell death. 5,6 In an attempt to clarify the role of mitochondria in apoptosis, we studied the expression of a number of proapoptotic mitochondrial proteins. 1,19 Unexpectedly, none of the tested proteins, including cytochrome c, AIF, Omi and Smac gave a positive signal in Western blot ( Figure 5, lane 1), whereas a mitochondrial isoform of superoxide dismutase (MnSOD) or the cytoplasmic protein Bax were readily detectable ( Figure 5, lane 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, compared with optimal dietary lipids levels, low or excess levels of lipids upregulate the caspase 3, caspase 7, caspase 8 and caspase 9 mRNA levels in the head kidney and spleen of young grass carp, suggesting that low or excess levels of lipids could increase apoptosis, whereas supplementation with optimal lipids could reverse this increase in the caspase mRNA levels in the head kidney and spleen of young grass carp. The B-cell lymphoma-2 (Bcl-2) family is an important class of regulatory proteins, which regulate apoptosis at the mitochondrial level [103]. In human cells, they can be divided into anti-apoptotic (such as Bcl-2) and pro-apoptotic (such as Bax) proteins according to their function [104].…”
Section: 32mentioning
confidence: 99%
“…8 Furthermore, it reduces spontaneous apoptosis of neutrophils in vitro. 16,17 In vivo, the clinical effects of G-CSF are also related to its antiapoptotic properties. It is routinely used to overcome neutropenia after chemotherapy, and to treat severe congenital neutropenia in Kostmann syndrome.…”
Section: Introductionmentioning
confidence: 99%